KONTRIBUSI STABILITAS EMOSI DAN KOMPETENSI DIRI TERHADAP KEPUASAN KERJA GURU DI MADRASAH ALIYAH NEGERI KABUPATEN BENER MERIAH - Muhammad Syarif, Amiruddin Siahaan, Candra Wijaya (Program Studi Pendidikan Islam Pascasarjana UIN Sumatera Utara Medan, 2018)
Abstract:This research aims to determine: (1) Emotion stability contribution toward satisfyingly teacherworking, (2) Self-competition contribution toward satisfyingly teacher working, and (3) Emotion stabilityand Self-competition contribution toward satisfyingly teacher working. This research is Ex-post factoresearch. The location of research is MAN Bener Meriah regency, which is three school’s, they are: MAN1, MAN 2 and MAN 3. The population in this research were 94 students, the method of collecting dataused in a closed questionnaire with Likert scale. The technique of analysis data include: (1) instrumenttest, validity and reliability. (2) Test prerequisites research, consisting of normality, linearity and homogenitytest. (3) The hypothesis test, used analysis simple regression and analysis multi regression of three predictors.The result of this research were: (1) There are positive and significant the effect of Emotion stabilitycontribution toward satisfyingly teacher working of power is 0,530 or 53,0%. (2) There are positive andsignificant the effect of Self-competition contribution toward satisfyingly teacher working of power is 0,664or 66,4%. (3) There are positive and significant the effect of Emotion stability and Self-competition contributiontoward satisfyingly teacher working with the influence of power is 0,749 atau 74,9%.Kata Kunci: Emosi, Stabilitas dan Kepuasan